I OBJECT. - Walsh, Maria (Art Monthly, 2013)
In this article, the author discusses how various contemporary artists are choosing to abandon the "subject position" and giving up control and autonomy over their work in favor of becoming objects or a type of objecthood. Artists discussed include Ed Atkins, Andy Holden, Hito Steyerl, and Mark Leckey. In addition, the author comments on the work of the sociologist Bruno Latour.